MDM2 gene polymorphism and endometrial cancer risk - Zając, Agnieszka; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2009)
Endometrial carcinoma makes one of the main problems in gynecological oncology of the menopausal period. Lack of screening for this neoplasm is a reason for the importance of the studies occupied in genetic background of this carcinoma. In this context the searching for connection between MDM2 gene, its polymorphism and the risk of endometrial carcinoma plays an important role. If its results have clinical importance, time will tell.